Vozes, escuta e silêncio dos alunos acerca da avaliação da aprendizagem no contexto de um curso de pedagogia no município de Guanambi-Bahia - Jose Aparecido Alves Pereira (2010)
This research has as goal to understand the assessment practices of learning evaluation, emphasized in the researchers dialogue with twenty students intentionally chosen by Pedagogy Course/UNEB, Campus XII, day and nighttime, in order to verify through the voices, listening and the silence, which were the thoughts that they had about the curriculum practice. In other words, to evaluate this courses development in order to arbitrate how this course approached from the participative, democratic and emancipatory practice like is proposed its curriculum. The assumption was made that the discuss interpretation from the students as the the voices, listening or silence which would related during the interviews made with the participants from this research and the documental analyses from the Pedagogical Course curriculum would illustrate the assessments curriculum, as well as would show the students assessment about the curriculum quality and the evaluative practices used during the development of Pedagogy Course. The research object, to understand who are the subjects, constitutes the first research question, and this defined the necessity to know the students profile, using a questionnaire that centered in variables from geopolitical, socio-economical and cultural territory, was a reference point to find the intentional sample. The interpretative analysis was made following many authors, mainly Freire and Bakhtin. The methodology central point was the evaluation of the curriculum practices, with the data collected through the interview with open and semi-structured questions, from the students behavior in the disciplines and complementary activities related like political expressions, that qualified the teachers pedagogical work, experienced in the classes, group work, during seven semesters. The results summarized points that is near the curriculum quality, like the theoretical-practical proposed that aims the pedagogue human, ethnical, political and democratic formation. Regarding the dimension curriculum practice, the students revealed difficulties in the interdisciplinary articulation from the disciplines of each period of Pedagogic Course, as well as the research absence as educative principle and the barriers and the conflicts between theory and practice. The whole process was and is opened to be criticize and facilitators suggestions in order to process the questions encountered in the praxis and poiesis of new investigations about the Pedagogy Course.